The Marian Apparition and Christian Arduous Hope Amid Political Repression: The Case of Our Lady of La Vang in Eighteenth-Century Vietnam - Duong, Bien Van (Department of Political Sciences, Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2025)
This article sheds new light on the multifaceted dimensions of hope experienced by Vietnamese Christians who reportedly witnessed a Marian apparition at the La Vang site in the context of eighteenth-century Vietnam’s political turmoil. Through examining the signs of hope in the case of the alleged Marian apparition at La Vang, the study reinforces Thomas Aquinas’s idea of hope as an arduous journey—difficult but possible to attain—in helping Christians cope with trauma under political repression. The first section outlines the research approach, combining historical-political and philosophical perspectives. The second section situates the presumed Marian apparition at La Vang within its historical framework, highlighting the socio-political context of the time. The third section explores the messages of hope conveyed through the alleged apparition of the Blessed Virgin Mary at La Vang. Finally, using the case of Our Lady of La Vang, the article concludes by affirming the significant role of religious faith in comforting believers amid political catastrophe.